INSTITUTIONAL TRANSFORMATIONS IN THE TURKESTAN REGION: FORMATION OF CHANNELS FOR RUSSIAN CAPITAL (LATE 19TH - EARLY 20TH CENTURIES) - Ismoilova, Parvina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The paper is devoted to the study of institutional transformations in the Turkestan region in the late 19th - early 20th century, which were aimed at creating favorable conditions for attracting Russian capital. The study focuses on analyzing the key changes in the legal system, infrastructure, and financial sphere, as well as on identifying the impact of these transformations on the development of Turkestan's economy.